2018
DOI: 10.1038/s41586-018-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear ARP2/3 drives DNA break clustering for homology-directed repair

Abstract: DNA double-strand breaks repaired by non-homologous end joining display limited DNA end-processing and chromosomal mobility. By contrast, double-strand breaks undergoing homology-directed repair exhibit extensive processing and enhanced motion. The molecular basis of this movement is unknown. Here, using Xenopus laevis cell-free extracts and mammalian cells, we establish that nuclear actin, WASP, and the actin-nucleating ARP2/3 complex are recruited to damaged chromatin undergoing homology-directed repair. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
394
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(443 citation statements)
references
References 41 publications
16
394
3
Order By: Relevance
“…These functions are mainly regulated via spatiotemporally-controlled polymerisation of monomeric actin into filamentous actin (F-actin). Although actin is largely perceived as a cytoplasmic protein, transient F-actin is observable within eukaryotic nuclei 5 , where it is involved in a variety of cellular processes such as the serum response 6 , cell spreading 7 , mitotic exit 8 and DNA repair [9][10][11] .…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…These functions are mainly regulated via spatiotemporally-controlled polymerisation of monomeric actin into filamentous actin (F-actin). Although actin is largely perceived as a cytoplasmic protein, transient F-actin is observable within eukaryotic nuclei 5 , where it is involved in a variety of cellular processes such as the serum response 6 , cell spreading 7 , mitotic exit 8 and DNA repair [9][10][11] .…”
Section: Main Textmentioning
confidence: 99%
“…These functions are mainly regulated via spatiotemporally-controlled polymerization of monomeric, or globular, actin (G-actin) into filamentous actin (F-actin). Although actin is largely perceived as a cytoplasmic protein, transient F-actin occurs within eukaryotic nuclei (8), where it is involved in a variety of cellular processes such as the serum response (9), cell spreading (10), mitotic exit (11) and DNA repair (12)(13)(14). Recently, it was suggested that actin dynamics in G1 phase promote replication initiation through transcription regulation (15).…”
Section: Main Textmentioning
confidence: 99%
“…In flies, a similar actin/myosin-based mechanism moves DSBs for repair 8,18 . Importantly, in a given cell, carcinogens can trigger several DSBs that co-localize and create a DNA repair centre, which is enriched in Rad52 in yeast but remains poorly understood across eukaryotes 17,19 . The forces driving DSB clustering, whether such forces crosstalk with nuclear filaments, and how clustering promotes genome stability remain unclear.Therefore, we used a yeast system for the fluorescence-based visualization of DSBindicating Rad52, a-tubulin Tub1, and NPC-indicating Nup49 protein 16 ( Supplementary Fig.…”
mentioning
confidence: 99%
“…A novel mechanism that mediates DNA relocalization emerged from recent literature, whereby polymerization of nuclear F-actin filaments was shown to facilitate the mobilization of damaged DNA towards the nuclear periphery. This included the directed movement of heterochromatic DSBs in D. melanogaster and stalled replication forks in human cells towards the nuclear envelope (Ryu et al 2015;Caridi et al 2018;Lamm et al 2018;Schrank et al 2018). To investigate telomere targeting to the nuclear periphery, we visualized the three-dimensional telomere localization in cells harboring mutant POT1.…”
Section: Pot1 Dysfunction Promotes F-actin Dependent Telomere Localizmentioning
confidence: 99%